Reproductive Morphology and Beraviour of Menochilus Sexmaculatus Fabr. (Coleoptera: Coccinellidae) - Malsin, Navies (1997)
Reproductive behaviour of ladybird, Menochilus sexmaculatus Fabr. (Coleoptera: Coccinellidae) reared on aphid infesting groundnut, Aphis craccivora Koch (Homoptera: Aphididae) was studied. The sex of adult M sexmaclilatus can be morphologically distinguished by comparing the edge of last visible segment (8th stemite); where it is concave in male and round in female. Additional characteristics that can be used to determine the sex of the adult are the trachea arrangement in the abdomen (irregular in male and nearly straight longitudinal line in female), the shape of the posterior part of the body (rounded in male and oval in female), and the relative size of the adult (the male smaller than the female). The males recognize their mate visually (body shape and movement), chemically (body odour and chemical on the body surface of the female) and by tactile (body surface texture). The male also displays aggression during mating. The bigger male appeared dominant over the smaller one. The sequence of behaviour of male during mating IS, "approach", "walk or run", "examine" by vibrating its maxillary pulps, "mount" and "copulate". While copulating, the male shook its body, licked, tapped (by its maxillary pulps) and rubbed (by its front and middle tarsi) the dorsal surface of female's elytra. The function of body shaking was to ensure a successful sperm transfer and likewise the licking and tapping behaviours are for copulatory courtship. The duration of copulation was not significanly different between virgin (97.6 ± 9.1 minutes) and mated (101.8 ± 5 4 minutes) pairs. The latent period of body shaking and the duration of post-copulation mOlmting were 3.7 ± 0.2 seconds and 51.0 ± 5.8 seconds, respectively. The number of body shaking was significantly (P<0.01) determined by the duration of copulation, and the relationship can be expressed as a logistic function. Mating behaviour in M sexmaculatus occurred mostly during the day with two peaks at 0900 hr to 1100 hr and 1500 hr to 1900 hr. Oviposition activity fluctuated following the day and night cycles with no regular patterns. Mating and oviposition activity may be regulated by temperature and relative humidity as expressed by a quadratic function. The predicted optimum temperature and relative humidity for reproductive activity were 31.7 ± 0.5°C and 53.1 ± 4.3%RH, respectively. When food became scarce, the percentages of mating and oviposition were low as the adult predators spent more time in searching for food. Frequent mating in M sexmaculatus did not influence fecundity, percent egg hatch and egg weight. The number of eggs laid per day, percent egg hatch and egg weight of M. sexmaculatus were influenced by age of the adult female and nutrient quality. The relationship between percent egg hatch with egg weight, percent egg hatch with total eggs laid per female per day, and total eggs laid per female per day with egg weight were expressed by the increasing linear equation, decaying exponential equation and decreasing linear equation, respectively. Younger females of M sexmaculatus produce more viable eggs.